2014
DOI: 10.1111/cyt.12131
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial carcinoma in high‐risk populations: is it time to consider a screening policy?

Abstract: Endometrial carcinoma (EC) is the leading female genital tract malignancy in industrialized countries. It will become an important public health problem in the coming years in the USA and Europe, where its incidence is increasing, and next-generation interventions should include periodical screening in high-risk women. In this review, we discuss the importance to gynaecologists of detecting women at high risk and offering an adequate screening programme. Screening for EC is particularly challenging and there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 47 publications
(102 reference statements)
0
25
0
Order By: Relevance
“…In the UK, there was an increase from 13.5 to 20.3 per 100,000 considering 1993 and 2010 [3]. In Europe, the latest report from 2012 considering corpus uteri cancer show an incidence from 14 to 29 per 100,000 and a mortality rate rounding 4 for 100,000 (http://globocan.iarc.fr).…”
Section: Endometrial Cancer Epidemiology and Diagnosismentioning
confidence: 99%
“…In the UK, there was an increase from 13.5 to 20.3 per 100,000 considering 1993 and 2010 [3]. In Europe, the latest report from 2012 considering corpus uteri cancer show an incidence from 14 to 29 per 100,000 and a mortality rate rounding 4 for 100,000 (http://globocan.iarc.fr).…”
Section: Endometrial Cancer Epidemiology and Diagnosismentioning
confidence: 99%
“…First reports evaluating asymptomatic women showed that fragments of tissue obtained by devices comparable to pipelle were very valuable in the diagnosis of endometrial cancer, contrary to endometrial smears . Interpretation of endometrial smears has been hampered in the past years by excess of mucus and blood, and overlapping cells . However, the introduction of liquid‐based technologies in the past years has reduced these flaws and helped improving the accuracy of endometrial cytology .…”
Section: Minimally Invasive Gynecologic Sampling Methods To Detect Enmentioning
confidence: 99%
“…104,105 Interpretation of endometrial smears has been hampered in the past years by excess of mucus and blood, and overlapping cells. 106 However, the introduction of liquid-based technologies in the past years has reduced these flaws and helped improving the accuracy of endometrial cytology. 106 Endometrial smears have been used in Japan in mass early detection programs (among symptomatic ≥50 aged women attending a cervical cancer screening program), which showed the identification of less aggressive cancers compared to the regular diagnoses in the outpatient clinics.…”
Section: Minimally Invasive Gynecologic Sampling Methods To Detect Enmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are no known reliable diagnostic and prognostic biomarkers for EC. Cancer antigen 125 (CA125), being most frequently used as a biomarker for ovarian cancer, has some diagnostic/prognostic value in EC [3]. However, CA125 level is elevated in a number of physiological and pathological conditions, such as age [4,5], pregnancy [6], menstruation [4,6], and in gynaecological and nongynaecological disorders, such as endometriosis [6], benign ovarian cysts [6], pelvic in ammatory disease [6], peritonitis [6], pancreatitis [6], and pneumonia [6].…”
Section: Introductionmentioning
confidence: 99%